1996
DOI: 10.1002/j.1460-2075.1996.tb00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a titratable lysine residue that determines sensitivity of kidney potassium channels (ROMK) to intracellular pH.

Abstract: Potassium (K+) homeostasis is controlled by the secretion of K+ ions across the apical membrane of renal collecting duct cells through a low‐conductance inwardly rectifying K+ channel. The sensitivity of this channel to intracellular pH is particularly high and assumed to play a key role in K+ homeostasis. Recently, the apical K+ channel has been cloned (ROMK1,2,3 = Kir1.1a, Kir1.1b and Kir1.1c) and the pH dependence of ROMK1 was shown to resemble closely that of the native apical K+ channel. It is reported he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
195
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(215 citation statements)
references
References 39 publications
16
195
2
Order By: Relevance
“…2 A). Similar observations for ROMK1 and ROMK2 have been reported by others (8,10). The half-maximal inhibitory pH values, pH 0.5 , and Hill coefficients of the isoforms were not significantly different (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2 A). Similar observations for ROMK1 and ROMK2 have been reported by others (8,10). The half-maximal inhibitory pH values, pH 0.5 , and Hill coefficients of the isoforms were not significantly different (Fig.…”
Section: Resultssupporting
confidence: 89%
“…1) produced pH-insensitive channels (8,10,14); however, a more complete pH titration to 4 demonstrated that each of the three ROMK isoforms remained pH sensitive, with the N-terminal K3 M mutation ( Fig. 2 B and C).…”
Section: Resultsmentioning
confidence: 96%
“…These data suggest a possibility that pH i -sensitive K ϩ channels usually have the specific pH i -sensitive site in the channel protein. Although the mechanism of pH i -sensitivity in the BK channel of RPTECs is still unknown, our conclusion that H ϩ regulates the activity of this BK channel by binding to the site distinct from Ca 2ϩ sites is supported by findings in the above recent reports [35][36][37]. It is quite likely that H ϩ inhibited the channel activity mainly by the allosteric reduction of the Ca 2ϩ binding affinity.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, a recent report using mSlo3, a member of the BK channel family sensitive to pH i rather than to Ca 2ϩ , provided evidence that the pH i -sensitivity of this channel is independent of Ca 2ϩ -sensitivity [35]. Furthermore, it has also been demonstrated in a cloned pH i -sensitive K ϩ channel, K ir 1.1 (ROMK), that an intracellular lysine close to the M1 segment, composing the pore region, has been identified as the structural element necessary for pH idependent gating [36,37]. These data suggest a possibility that pH i -sensitive K ϩ channels usually have the specific pH i -sensitive site in the channel protein.…”
Section: Discussionmentioning
confidence: 96%
“…We therefore examined the effect on glutamine uptake of lowering the internal pH of ASCT2-expressing oocytes by adding increasing concentrations of HCO 3 Ϫ to the incubation solution. Raising the concentration of HCO 3 Ϫ in the incubation solution from 0 to 90 mM for 15 min has been shown to lower the cytosolic pH of oocytes by ϳ1 unit (Fakler et al, 1996). Under these conditions we observed a modest decrease of glutamine uptake (Table 1).…”
Section: Glutamine Uptake In Asct2-expressing X Laevis Oocytesmentioning
confidence: 57%